Optimalisasi pembelajaran berbasis praktisi BPBD dan bnpb pada mata kuliah sistem mitigasi bencana - Hasbi, Hasbi Nur Prasetyo Wisudawan (Universitas Islam Indonesia, 2024)
The aim of this research is to optimize practitioner-based learning in the Disaster Mitigation Systems course to increase student motivation and understanding regarding technology, management and disaster mitigation. Learning design involves collaboration between lecturers and practitioners from BPBD and BNPB, with a project-based approach. The results showed that engaging practitioners in their areas of expertise provided real, relevant insights, while social media-based group projects improved students' collaboration and communication skills. Evaluations show a student pass rate of 98%, with feedback. Challenges faced include combining classes and technical limitations in hybrid mode. The sustainability of practitioner lectures can be strengthened by field visits, integration of MBKM activities, and increased focus on aspects of mitigation technology.